Cryptococcoid Sweet syndrome: a case report - Volonté, Martina; Fiandrino, Giacomo; Vassallo, Camilla; Barruscotti, Stefania; Giorgini, Chiara; Tomasini, Carlo Francesco; Brazzelli, Valeria (Frontiers in Medicine, 2024)
Cryptococcoid Sweet syndrome (cSS) is a recently described clinical and histological variant of Sweet syndrome (SS). Its cutaneous presentation is similar to the classical form of SS but it includes atypical findings, such as capsular and yeast-like structures on microscopy that are reminiscent of Cryptococcus species. However, in cSS, fungal staining and cultural examination are negative, whereas myeloperoxidase (MPO) staining on biopsy specimens is typically positive. Due to the rarity and the diagnostic challenge represented by this disease, its extracutaneous involvement, and the latency in its diagnosis, this condition is frequently associated with poor prognosis. In this study, we report the case of a cSS patient with a positive outcome.